Modeling and Simulation of Hybrid Energy Systems to Meet Dynamic Load Requirements - أمون, رشـــوان; محســن داود; ســامر ســليمان (Latakia University Journal -Engineering Sciences Series, 2022)
This research presents the study of a hybrid energy system which consists of a group of photovoltaic cells as well as a group of wind turbines connected to the main electric power supply network based on fossil fuels, in order to reduce the demand for this fuel - which is harmful to the environment and depleted with time - especially in times when we are able to invest renewable energies on sunny days and days when the wind is suitable. Furthermore, this approach meets the requirements of dynamic loads changing at all times, especially in the hours of peak energy demand. The modeling operations are achieved in the Matlab/Simulink environment. The simulation was performed for a full day with different weather parameters (Solar radiation and wind speed) and the parameter of changing demand for energy during the hours of the day. Finally, the results are presented and discussed. They show an effective saving in fossil fuel consumption in varying proportions depending on the amount of energy extracted from solar cells and wind turbines, which depends in turn on the intensity of solar radiation and the appropriate wind speed. The best result appears clearly at 12 noon, which is the peak of energy consumption over the day. This leads to playing a major economic role in the field of energy .